Paysage digital : une expérimentation visuelle du sensible sur la Goule aux fées - Corinne Feïss-Jehel; Pierre-Jérôme Jehel (Projets de Paysage)
This article investigates an artistic project focusing on a site within a landscape. It involves a project entitled "Une origine du monde des images. La caverne des Lumière" (An Origin of the World of Images. The Cavern of Light), and a digital series. The sea cave, known as La Goule aux Fées, is located on the north coast of Brittany. The landscape is observed by means of a variety of experimental media in reference to the Lumière brothers’ visit to the area. The series studied is a a digital recording of a series of digital images of the site. The relevance of these techniques is based on the history of the site and results in a sensory approach to how the cave is perceived.